Requalificação de hospitais: um estudo sobre intervenções físico-espaciais em dois grandes edifícios hospitalares em Belo Horizonte, Minas Gerais, Brasil - Márcia Campos Moreira Tofani (2013)
This study consists in a contribution towards a better understanding on the processes of architectural redevelopment of large hospitals, as well as: their main motivations, relationships, and implications in the context of hospital activities; the hospital organization; the hospital management and planning; and hospital architectural design. A large hospital is a privileged space for accumulation of scientific and technological knowledge of the Health Sciences and consists, fundamentally, of a space produced and organized for research, diagnosis and therapy. As such, it is home to a great complexity and variety of functions and equipment and has a building infrastructure with few correspondents in architecture. This complexity and variety make large hospital architectural design highly conditioned by technical issues and constitutes it one of the most challenging fields of architecture. This condition of hospital architecture takes shape even more intricate when one considers that the spatial production and organization of hospital buildings are characterized by continuous transformation. As far as hospital buildings are highly conditioned by technical issues, and rely on them, they are highly susceptible to the development of scientific and technological knowledge of health sciences, their methods and techniques of care, diagnosis and therapy and legal regulations. This is mainly manifested in the need to undertake space and infrastructure renovation to allow the hospital to work properly. However, the process of architectural redevelopment of large hospitals is characterized by facing further difficulties such as the high cost of hospital facilities, the usual financial limitation of hospital institutions and, above all, the growing demand for health services assistance by the population. This study identifies and analyzes the motivations, characteristics and conditions of physical-spatial interventions in large hospitals, pointing out the difficulties faced in the design and built process, as well as the relationship between these interventions and hospital planning and hospital activities. Therefore, we analyzed two large general hospitals: a public university hospital named Hospital das Clínicas da Universidade Federal de Minas Gerais (HC/UFMG), and a private one named Semper Hospital. Both are located in the city of Belo Horizonte, state of Minas Gerais, Brazil.